2004
DOI: 10.1038/sj.leu.2403311
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate associated with delayed hematopoietic recovery after concomitant chemotherapy

Abstract: results indicate that the absolute degradation rate is approximately 50% per day (ie an increase of the Ct value with one cycle) in PB MNC.Although our data are based on a limited and heterogeneous set of samples, they clearly indicate that transcripts are rapidly degraded ex vivo and that the rate of degradation can differ between different types of transcripts, between PB and BM, and between patients. As such differential degradation will results in an over-or underestimation of MRD levels, samples should pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Despite the relatively high specificity of IM treatment towards the BCR-ABL fusion protein, off-target multikinase inhibitory effects occur and can interfere with normal hematopoiesis. 1, 2 For instance, non-specific inhibition of Flt3L has been associated with disruption of dendritic cell (DC) homeostasis and functions in both mice and humans. 3 In addition, studies have reported an interference of IM with T cell counts and activation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively high specificity of IM treatment towards the BCR-ABL fusion protein, off-target multikinase inhibitory effects occur and can interfere with normal hematopoiesis. 1, 2 For instance, non-specific inhibition of Flt3L has been associated with disruption of dendritic cell (DC) homeostasis and functions in both mice and humans. 3 In addition, studies have reported an interference of IM with T cell counts and activation.…”
Section: Introductionmentioning
confidence: 99%